Electrons in solids : an introductory survey - Bube, Richard H., 1927- (Academic Press, 1992)
This Third Edition of ELECTRONS IN SOLIDS: AN INTRODUCTORY SURVEY, is the result of a thorough re-examination of the entire text, incorporating suggestions and corrections by students and professors who have used the text. Explanations and descriptions have been expanded, and additional information has been added on high Tc superconductors, diamond films, "buckminsterfullerenes," and thin magnetic materials. Adopted by many colleges and universities, this text has proven to be a solid introduction to the electrical, optical and magnetic properties of materials. Key Features * Contains comprehensive coverage of electronic properties in metals, semiconductors, and insulators at a fundamental level * Stresses the use of wave properties as an integrating theme for the discussion of phonons, photons, and electrons * Includes a complete set of illustrative problems along with exercises and answers * Features a careful indication of both Gaussian and SI unit systems.